Manajemen Kepemimpinan Berbasis Agama dan Psikologi - Supatmin Supatmin; Sugeng Wardoyo; Toto Sunarto; Sofyan Sauri; Faiz Karim Fatkhullah (Edulead : Journal of Education Management, 2021)
This journal aims to find out how to be a principal for religion and education to find out how to be a leader based psychology at the al-amien, ciater serpong. This is kind of research with fenomenologis. quantitative approach A source of the data obtained by the primary data. Data collection techniques, observation, interview, documentation and triangulation. Data analysis techniques with descriptive, analytical namely by, data was display data and draw conclusion. Among other issues discussed what defines a religion based education leaders as well as being a leader based education psychology at the al-amien, ciater serpong